The Impact of Tourism Development in Pamah Simelir Hamlet Telagah Village, Langkat Regency - Ramses Ginting; Annisa Ilmi Faried; Anggia Ramadhan (Journal of Research in Social Science and Humanities, 2025)
This thesis examines the impact of tourism development in Pamah Simelir Hamlet, Telagah Village, Langkat Regency. This descriptive qualitative research involves interviews with various related parties to understand the changes that have occurred. The results show significant positive economic impacts, such as increased community income (up to 80% for MSMEs), creation of new jobs, and increased land prices. Socially, there has been increased access to education and health, as well as changes in more open social interactions. However, this development also has negative environmental impacts, including conversion of agricultural land, increased volume of unmanaged waste, and decreased water quality. In addition, coordination with investors is still a challenge. In conclusion, tourism in Pamah Simelir brings great benefits, but requires sustainable management and strong collaboration between the government, managers, and the community to minimize negative impacts and maximize the potential of the region.